Antimicrobial activity and cellulose acetate membrane characterization with tangerine peel extract (Citrus reticulata) for bio packing - RFM, Rachel F Magnago Magnago; Tutida, Alessandra Yula; Piovezan, Anna Paula; Mazon, Simone Perroni; Consoni, Deise; Girotto, Edivandro; Egert, Paola; Silva, Heloisa Regina Turatti; Zanco, Jasper; Souza, Morgana; Walber, Thais Andressa; Valezan, Igor Fagundes; et al. (Ciência e Natura, 2022)
Biopacking material was obtained by incorporating tangerine peel extract (Citrus reticulata) in cellulose acetate (CA) film. The acetate film with tangerine extract was shown to have a homogeneous material characteristic by FTIR and DSC analysis, being reinforced in MEV and MFA, and showed absence of pores in the film with extract. These characteristics justify the reduced water absorption and release of the CA membrane extract. Low water absorption is important for the film to act as a barrier with external environment and the release of the extract was sufficient to prevent the growth of the strains investigated on the sample surface. The introduction of the extract also reduced the tensile strength and deformation of the film. This study showed the good potential of biomass for active bio packing that can gradually replace non-renewable packaging and take advantage of agricultural waste.